Team tools for early assessment in math Teacher´s guide
Tools for Early Assessment in Math (TEAM) is an assessment screening tool for students in Grades PreK?5. This tool can be used to determine where a student is proficient in math skills by providing meaningful diagnostic reports and by prescribing additional activities to accelerate their learning of these skills based on the reported data.